Spatial distribution of organic-walled dinoflagellate cysts in surface sediments from the southern Caribbean Sea and eastern tropical Pacific Ocean (2016)
Numerous global studies of organic walled dinocyst distribution and their relation with the environment have been done across temperate regions, however neotrotropical oceans, are underrepresented, and the paleoceanography, paleobiogeography and paleoecology of region has been underdeveloped. Caribbean Sea and Pacific Ocean present a complex interaction between atmospheric circulation and oceanic currents that have effects in global climate (e.g. North Atlantic Ocean dynamics and ENSO), being a region with valuable paleoecological informatlon deposited in sediments to study climate, sea level and geographic changes and also, to explore interactions between many organisms in several geologic periods. We analyzed 34 modem surface sediment samples from the Caribbean Sea and the tropical east Pacific Ocean (equator-16°N, and 62°W-85°W) to assess the spatial distribution of organic-walled dinoflagellate cysts assemblages in relation to surface oceanographic conditions (temperature, salinity, oxygen, nutrients, water depth, and distance to coast). Sediment samples display different cyst concentrations with values ranging from 51 to 6036 cysts/cm³ of sediment. A higher diversity of dinocysts was found near the Equator line for the Pacific Ocean. The dinoflagellate assemblage composition and cyst concentration showed a clear separation between the two regions. Partial redundancy analyses (pRDA) illustrated that geographic location (Caribbean/Pacific), phosphates, and sea surface salinity (SSS) were the most important factors controlling cyst assemblage distribution in the area. The variance explained by the environment was 41%, by location 21%, and by joint environment and location 45%. The terrestrial influence (river discard) was analyzed from the pollen grains and spores of ferns counted of each sample and using a terrestrial/marine index. This study represents the first survey of recent organic-walled dinoflagellate cysts in the Caribbean and eastern tropical Pacific waters, and provides a regional dinocyst baseline that could be used in tropical paleoceanographical, paleoenvironmental and paleobiogeographical reconstructions.